Translational Significance of Heme Oxygenase in Obesity and Metabolic Syndrome - Abraham, Nader G. (Trends Pharmacol Sci, 2015)
The global epidemic of obesity continues unabated with sequelae of diabetes and metabolic syndrome. This review reflects the dramatic increase in research on the role of increased expression of heme oxygenase (HO)-1/HO-2, biliverdin reductase, and HO activity on vascular disease. The HO system engages with other systems to mitigate the deleterious effects of oxidative stress in obesity and cardiovascular disease (CVD). Recent reports indicate that HO-1/HO-2 protein expression and HO activity have several important roles in hemostasis and ROS-dependent perturbations associated with metabolic syndrome. HO-1 protects tissue during inflammatory stress in obesity through the degradation of pro-oxidant heme and the production of carbon monoxide (CO) and bilirubin, both of which have anti-inflammatory and anti-apoptotic properties. In contrast, repression of HO-1 is associated with increases of cellular heme and inflammatory conditions including hypertension, stroke and atherosclerosis. HO-1 is a major focus in the development of potential therapeutic strategies to reverse the clinical complications of obesity and metabolic syndrome.